Etnopedagogy of BEKANA as an Informal Education Method for Preschool Children in the Dayak Kebahan Community of Sintang - Yuliono Evendi; Ridwan Tonny Hasiholan Pane; Welikinsi Welikinsi; Karnodin Karnodin; Yeremia Yeremia; Agustina Ace Wagena (Attractive : Innovative Education Journal, 2026)
This study explores BEKANA, a traditional storytelling practice in the Dayak Kebahan community of Sintang, as an ethnopedagogical method of informal education for preschool children. BEKANA is not merely a teaching technique but also a medium of communication that fosters closeness between parents and children while transmitting cultural values. In the current era of rapid scientific and technological advancement, children increasingly consume stories through digital platforms such as mobile phones and YouTube, which often lack cultural depth and parental involvement. This research aims to analyze the role of BEKANA in preserving local wisdom and strengthening parent–child bonds within informal education settings. Using a qualitative approach with ethnographic methods, data were collected through interviews, observations, and documentation involving parents, community elders, and preschool children. The findings reveal that BEKANA serves as a vital tool for cultural transmission, character building, and emotional connection between generations. It provides children with moral lessons, linguistic enrichment, and cultural identity rooted in Dayak Kebahan traditions. The study concludes that revitalizing BEKANA in informal education can counterbalance the dominance of digital storytelling, ensuring that children not only learn but also inherit the cultural heritage of their community.